Linking JCE WebWare to JCE Articles - William F. Coleman; Randall J. Wildman (Journal of Chemical Education, 2002)
INTRODUCTION: Young-onset atrial fibrillation (AF) is increasingly recognized as a clinically distinct entity and heritable mechanisms may contribute to disease onset. Although pathogenic monogenic variants are increasingly identified in this population, their clinical phenotype and prognostic significance remain incompletely defined. AIMS: We sought to characterize the spectrum of genetic variants in patients with young-onset AF diagnosed at age 45 years or younger, identify clinical predictors of pathogenic variants, and evaluate their association with long-term clinical outcomes. METHODS: This multicentre retrospective cohort study included adults with AF first diagnosed at age 45 years or younger who underwent clinical genetic testing across three tertiary centers in Melbourne, Australia. Variants were re-assessed using contemporary American College of Medical Genetics and Genomics/Association for Molecular Pathology criteria and classified as pathogenic/likely pathogenic (P/LP) or negative/variant of uncertain significance (VUS). Baseline clinical characteristics, electrocardiographic findings, cardiac imaging, and long-term outcomes were compared between groups. RESULTS: Among 58 patients who underwent genetic testing, 30 (52%) had a pathogenic or likely pathogenic monogenic variant. The most frequent variants involved TTN (n = 8, 13.8%) and LMNA (n = 6, 10.3%), followed by MYBPC3 and MYH7 (each n = 3, 5.2%). Family history of AF or cardiomyopathy was more common in the P/LP than the negative/VUS group (76.7% vs. 46.4%, p = 0.030) and was independently associated with a pathogenic variant (OR 3.90; 95% CI 1.28-13.0; p = 0.020). Patients with pathogenic variants more frequently had first-degree atrioventricular block (20.0% vs. 0.0%; p = 0.024). Implantable cardioverter-defibrillator implantation was more frequent in P/LP patients (53.6% vs. 25.0%; p = 0.05), whereas mortality, stroke, post-ablation AF recurrence, and pacemaker implantation were similar. CONCLUSIONS: In this highly selected young-onset AF cohort referred for genetic testing, pathogenic monogenic variants were common. There was a significant proportion of patients suffering adverse long-term events.